Six Sigma: Literature Review Analysis - Pradhan , Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Six Sigma (SS) methodology is now one of the most used methods in quality management since it benefits from enhancing process performance efficiency by recognizing and reducing the causes of production and business process defects and variability. Thus, literature on the SS topic has increased exponentially over the past decades; the large number of works on the SS field represents a good opportunity for a structured literature review of the articles to understand the evolutions of the concept, the fields of its application and possible development for further studies. The literature review was performed using a retrospective analysis of the key SS methods developed for both large and small companies to highlight specific aspects of the SS literature and some SS technique implementations. The assessment of the papers contained in literature is carried out by means of a test of Strengths Weaknesses. In addition, an assessment was carried out for those dealing with the application of the SS methodology to both large companies, Small & Medium Enterprises (SMEs), based on the compliance with some milestones identified as necessary for each SS system. Finally the paper argues as to the research field's potential future developments.